A graphical browser for hypermedia systems - Yong, Huan Loon (Faculty of Computer Science and Information Technology, 1995)
The purpose of this study is to build a graphical browser as the navigation interface to navigate through a very large hypermedia system looking for relevant document. Hyper-G is the chosen hypermedia system. It is a large system capable of holding a huge repository of documents, and the graphical browser aims to limit the document access only to the useful and relevant documents.